Do Sporty People Have Access to Higher Job Quality? - Charlotte Cabane (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
Very little attention has been paid to the impact of sports participation on the labour market in the European academic literature while it has received significant recognition in the United States. We consider sports practice as a way to improve or signal non-cognitive skills endowment. And it is known that non-cognitive skills are an important determinant of success in life. Therefore we decided to analyse its impact on the access to employment in Germany. We test the hypothesis that sporty people - ceteris paribus - have access to higher quality of job thanks to the non-cognitive skills they have or they are supposed to have. Using objective measures of job quality, we demonstrate that being sporty does matter and that its effect cannot be award to any other extracurricular activities.
Keywords: J24; J28; L83; I2; 330; Job quality; Sport; Non-cognitive skills; Sport; Freizeitverhalten; Erwerbsverlauf; Arbeitsplatz; Arbeitsbedingungen; Qualifikation; Einkommen; Industrieländer